Data hiding in medical images using encryption and steganography techniques - Nur Athirah, Abdul Razak (2019)
This paper presents securing the transmission of medical images over the Internet. The presented algorithms will be applied to medical data. This work presents a method that combines encryption, steganography and compression techniques for data transmission purpose. In this paper, for the sender side, the secret text will be encrypted using Advanced Encryption Standard algorithm and embedded into the chosen cover image using Least Significant Bit algorithm for more security. A stego-image will be generated and compressed using Discrete Cosine Transform to reduce the size of stego- image in order to save storage. In the receiver side, the inverse methods will be implemented in reverse order to get the cover image along with the secret text. MATLAB simulation tool is used to implement the chosen technique and also for further development. In the end of this research, the performance of the algorithm will be assessed in the aspect of mean square error and peak signal noise ratio to compare the results of the chosen method.